Loading celecoxib into solid lipid nanoparticles significantly enhanced the anticancer activity - Alajami, Hamdan; Fouad, Ehab; Ashour, Abdelkader Elbadawy Abbas; Kumar, Ashok; Yassin, Alaa Eldeen (2018)
Introduction: Celecoxib (CXB), COX-2 enzyme inhibitor, has been approved recently for the treatment of colorectal polyps. Solid lipid nanoparticles (SLN) have turned out to be an attractive carrier alternative to liposomes and polymeric nanoparticles due to superior stability and biocompatibility. This work aimed to optimize CXB-loaded SLN for colon delivery with high potential toward enhancing the anticancer activity. Methods: An ultrasonic melt-emulsification method was employed in this work for the preparation of SLN. Briefly, an emulsion was formed after mixing melted lipid with heated aqueous surfactant solution heated to equal temperature by probe-sonication and dispersed in chilled distilled water for 10 minutes. The physical attributes were characterized for their particle sizes, charges, morphology, and entrapment efficiency (%EE), in addition to DSC and FTIR. The in vitro drug release profiles were evaluated and the anticancer activity was examined utilizing MTT assay in three cancer-cell-lines; HT29, Daoy, and HepG2. Results: All the prepared SLN formulations exhibited particle sizes in the nano scale ranging from 238nm to 757nm. There was dependence on the type and ratio of the surfactant used and the nature of lipid combination. The zeta-potential values (mv) were mostly in the -30s mv indicating higher stability potential of all SLN formulations. The minimum %EE was found equal to 86.76% (F9) which is advantageous of the method for large scale production. The disappearance of CXB characteristic melting peak from DSC thermograms of all formulations elucidates the amorphous nature of the SLN-entrapped CXB. The SEM images indicated the spherical nature of the SLN and CXB loading. The in vitro release profile showed a slow constant rate with no burst release which is uncommon with SLN. Both F9 and F14 showed a complete CXB release within 24-hour with only 25% within the first 5 hours. This makes them suitable for colonic targeting. F9 exhibited a significant % cell death in the three tested cancer cell lines after only 24 hours incubation and maintained the effect for 72 hours. In the case of F14, the significant % cell death was achieved with HT29 cell line after 24 hours and only after 72 hours for HepG cells, while non-significant effect was observed with Doay cells. Conclusion/Implications: The produced CXB-loaded SLN showed unique properties of slow release with no burst in addition to high %EE. The anticancer activity was extremely significant for one formulation in both HepG and HT29 cells which is highly promising.